Peat replacement in horticultural growing media: Availability of bio-based alternative materials - Olivier Hirschler; Bernhard Osterburg; Holger Weimar; Sebastian Glasenapp; Marie-Friederike Ohmes (Johann Heinrich von Thünen-Institut, 2022)
Peat is a fossil material and is since decades the major growing media constituent for horticulture in Europe. Because of its climate impacts, some European countries developed national strategies to reduce peat use. A coordinated European action would bring fairer and more effective impacts than isolated national strategies. The replacement of peat is possible using alternative growing media constituents based on biomass. Potential limitations of the resource availability for the production of alternative growing media constituents is one of the major concerns of the growing media industry. Although this paper does not constitute a final evaluation, it aims to initiate further discussions and investigations on this aspect of peat reduction. We compare potential amounts for the supply and demand of raw materials for the production of wood fibres, composted bark, green compost and coir pith in European countries. Moreover, we discuss the economic and legal conditions for the availability of alternatives. Our findings suggest that the resource supply does not generally indicate a limitation to an extended use of alternative growing media constituents in Europe. In a maximal demand scenario, the amounts considered would also be sufficient to completely replace peat. However, in this scenario, the current supply for nationally sourced alternative materials could be scarce for some countries like the Netherlands or the Baltic States. Competition for wood resources, e.g., with the energy sector, could limit their use in the growing media sector. Moreover, the conditions set by the EU Fertilising Products Regulation (EU) 2019/1009 might hamper a large use of wood fibres as growing media constituent. For bark, green waste and coir by-products, an increased demand from the growing media sector may support mobilization of additional resources. For coir by-products, a future rise of the international demand might lead to a strong competition and an exhaustion of the world's potential. Transportation costs play an important role for the access to biomass potentials. They could be reduced with the development of the infrastructure for processing available resources. Other growing media constituents like Sphagnum are not significantly used today but could represent additional potentials for the replacement of peat in future. In order to avoid displacement effects, the focus of peat substitution should be set on potential amounts of biomass that are currently not or not fully used, or the creation of new potentials. – – Torf ist ein fossiler Rohstoff und seit Jahrzehnten der wichtigste Bestandteil von Substraten für den Gartenbau in Europa. Aufgrund der damit verbundenen Klimawirkungen haben einige europäische Staaten nationale Strategien zur Reduzierung der Torfnutzung entwickelt. Eine koordinierte europäische Initiative würde fairere und effektivere Wirkungen entfalten als isolierte nationale Strategien. Der Ersatz von Torf ist durch die Nutzung alternativer, biomassebasierter Ausgangsstoffe für Kultursubstrate möglich. Mögliche Begrenzungen der Ressourcenverfügbarkeit für die Produktion alternativer Kultursubstrate stellt eines der größten Bedenken der Erdenindustrie dar. Dieses Papier stellt zwar keine abschließende Evaluierung dar, es zielt aber darauf ab, weitere Diskussionen und Untersuchungen dieses Aspekts der Reduzierung der Torfnutzung zu initiieren. Dafür vergleichen wir die Angebots- und Nachfragemengen von Rohstoffen für die Produktion von Holzfasern, kompostierter Rinde, Grünkompost und Kokosfasern in europäischen Ländern. Anschließend diskutieren wir die ökonomischen und rechtlichen Rahmenbedingungen für die Verfügbarkeit von Torfsubstituten. Unsere Ergebnisse legen nahe, dass das Rohstoffangebot insgesamt keine Begrenzung für eine erhöhte Nutzung von alternativen Kultursubstraten in Europa darstellt. In einem Szenario mit maximaler Nachfrage würden die betrachteten Mengen ausreichen, um Torf vollständig zu ersetzen. In diesem Szenario könnte die aktuelle, nationale Versorgung mit alternativen Rohstoffen allerdings für einige Länder zu knapp ausfallen, beispielsweise in den Niederlanden oder den baltischen Staaten. Der Wettbewerb um Holzressourcen, z. B. mit dem Energiesektor, kann die Nutzung für die Substratherstellung begrenzen. Darüber hinaus könnten Anforderungen gemäß EU Düngemittelverordnung (EU) 2019/1009 eine umfangreiche Nutzung von Holzfasern als Ausgangsstoff behindern. Im Fall von Rinde, Grünkompost und Kokosprodukten kann eine erhöhte Nachfrage der Erdenindustrie zur Mobilisierung zusätzlicher Mengen beitragen. Für Kokosnebenprodukte kann ein künftiger Anstieg der Nachfrage zu einem verstärkten Wettbewerb und einer Erschöpfung des weltweiten Potentials führen. Transportkosten spielen eine wichtige Rolle für den Zugang zu Biomasse-Potenzialen. Diese können durch die Entwicklung von Infrastruktur für die Verarbeitung verfügbarer Biomasse-Ressourcen verringert werden. Andere Bestandteile von Substraten wie Torfmoose werden bisher in keinem signifikanten Umfang genutzt, könnten aber ein zusätzliches Potenzial für den künftigen Torfersatz darstellen. Um Verlagerungseffekte zu vermeiden, sollte der Schwerpunkt der Torfsubstitution auf Mengenpotenziale gelegt werden, die derzeit nicht vollständig genutzt werden, oder auf der Erschließung neuer Potenziale.
urn:nbn:de:gbv:253-202203-dn064753-4
Keywords: Q21; Q31; Q54; 630; growing media; horticulture; peat; peat alternatives; availability; biomass resources; Kultursubstrate; Gartenbau; Torf; Torfersatz; Verfügbarkeit; Biomasse